Functional Regulation of ZnAl-LDHs and Mechanism of Photocatalytic Reduction of CO2: A DFT Study - Dongcun Xu; Gang Fu; Zhongming Li; Wenqing Zhen; Hongyi Wang; Meiling Liu; Jianmin Sun; Jiaxu Zhang; Li Yang (Molecules, 2023)
Defect engineering and heteroatom doping can significantly enhance the activity of zinc-aluminum layered double hydroxides (ZnAl-LDHs) in photocatalytic CO2 reduction to fuel. However, the in-depth understanding of the associated intrinsic mechanisms is limited. Herein, we systematically investigated Zn vacancies (VZn), oxygen vacancies (VO), and Cu doping on the geometry and electronic structure of ZnAl-LDH using density functional theory (DFT). We also revealed the related reaction mechanism. The results reveal the concerted roles of VO, VZn, and doped-Cu facilitate the formation of the unsaturated metal complexes (Znδ+-VO and Cuδ+-VO). They can localize the charge density distribution, function as new active centers, and form the intermediate band. Simultaneously, the intermediate band of functionalized ZnAl-LDHs narrows the band gap and lowers the band edge location. Therefore, it can broaden the absorption range of light and improve the selectivity of CO. Additionally, the unsaturated metal complex lowers the Gibbs free energy barrier for effective CO2 activation by bringing the d-band center level closer to the Fermi level. The work provided guidance for developing LDH photocatalysts with high activity and selectivity.